Electrocardiographic recognition of the epicardial origin of ventricular tachycardias - Berruezo, Antonio; Mont, Lluis; Nava, Santiago; Chueca, Enrique; Bartholomay, Eduardo; Brugada, Josep (Circulation (New York, N.Y.), 2004)
Some ventricular tachycardias (VTs) originating from the epicardium are not suitable for endocardial radiofrequency ablation and require an epicardial approach. The aim of this study was to define the ECG characteristics that may identify an epicardial origin of VTs. We analyzed the 12-lead ECG recordings during epicardial and endocardial left ventricular pacing in 9 patients to verify the hypothesis that the epicardial origin of the ventricular activation widens the initial part of the QRS complex. Then, we analyzed the ECG pattern in 14 VTs successfully ablated from the epicardium after a failed endocardial approach (group A), in 27 VTs successfully ablated from the endocardium (group B), and in 28 additional VTs that could not be ablated from the endocardium (group C). Four distinct intervals of ventricular activation were defined and measured: (1) the pseudodelta wave, (2) the intrinsicoid deflection time in V2, (3) the shortest RS complex, and (4) the QRS complex. VTs from groups A and C showed a significantly longer pseudodelta wave, intrinsicoid deflection time, and RS complex duration compared with VTs of group B. There was no difference between groups A and C. A pseudodelta wave of > or =34 ms has a sensitivity of 83% and a specificity of 95%, an intrinsicoid deflection time of > or =85 ms has a sensitivity of 87% and a specificity of 90%, and an RS complex duration of > or =121 ms has a sensitivity of 76% and a specificity of 85% in identifying an epicardial origin of the VTs. ECG suggests VTs originating from the epicardium and those with an unsuccessful radiofrequency ablation from the endocardium.